International Monetary Fund Annual Report 1956. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1956)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1956. The report highlights that the world payments situation has in fact improved, restrictions have been further relaxed, the transferability of important currencies has been extended, and discrimination, especially that resulting from bilateral arrangements, has had less influence on the direction of trade. Progress in extending multilateral trade and payments has thus been maintained, although during the year there was no addition to the list of IMF members that have established formal convertibility of their currencies.